Perceived Social Support, Parental Notification, and Parental Engagement after Pelvic Inflammatory Disease among Urban Adolescent and Young Adults - Muñoz Buchanan, Cara R. (Pediatr Neonatal Nurs, 2016)
BACKGROUND: Urban adolescent and young adult women often require adult support throughout their transition to adulthood particularly regarding seeking healthcare. While confidentiality is crucial feature of care delivery, successful adherence to treatment can be multi-factorial. The purpose of this study is to determine factors associated with parental notification and engagement in self-care of young women diagnosed with Pelvic Inflammatory Disease (PID). METHODS: This study utilizes data from 187 participants in the Technology Enhanced Community Health Nursing (TECH-N) study, a randomized controlled trial of an intervention to prevent recurrent STIs after a diagnosis of mild-moderate PID. Participants were recruited from pediatric ambulatory settings provided baseline demographic, reproductive history, and perceived social support using an audio computerized self-interview at baseline and parental notification collected during a two-week follow-up interview, served as the primary outcome. RESULTS: Sixty-five percent of participants informed a parent of their PID diagnosis, 74% of whom reported receiving supportive care. Participants who reported a higher sense of responsibility to others were 17% less likely to inform a parent of their diagnosis. CONCLUSION: Most urban young women with PID notify parents of their diagnosis and obtain support for self-management in the outpatient setting. While autonomy is a critical milestone for transition to young adulthood, these data suggest that proactive youth-managed parental engagement may be an underutilized resource for young women diagnosed with PID.